The Budget of Turbulent Kinetic Energy during Premonsoon Season over Kharagpur as Revealed by STORM Experimental Data. (16th September 2013) - Tyagi, Bhishma; Satyanarayana, A. N. V.
Abstract : Turbulent kinetic energy (TKE) budget variations during thunderstorm days (TD) and nonthunderstorm days (NTD) of premonsoon seasons of 2007, 2009, and 2010 have been investigated at a tropical station Kharagpur (22°30′N, 87°20′E) using the surface layer turbulence data obtained during severe thunderstorms-observations and regional modeling (STORM) experiment. Significant variations in the contributions of the TKE budget parameters with respect to stability are observed on these contrasting days of weather activity. In highly unstable conditions, smaller dissipation rates are seen on TD compared to NTD, while approaching near neutral conditions, higher dissipation rates are found in TD. New relationships between TKE dissipation rates with respect to atmospheric stability are proposed at Kharagpur for TD and NTD.